"No, it is a hobby for me": Examining the motivations of non-Irish learners of the Irish language in North America. (March 2016) - Giles, Jonathan
Abstract: This paper examines how non-Irish learners of Irish Gaelic in Ontario, Canada navigate through questions of authenticity and legitimization as members of the Irish language network. Learners without Irish heritage often convey a happenstance or hobby-like connection, which stands in contrast to motivations common in the Irish diaspora that often connect with participants' sense of who they are as Irish people. Despite viewing their connection as hobby-like, many are fluent speakers with longstanding involvement in the network, and are legitimized by sharing ideologies that stress an ancient quality to the language, and as musicians or holders of valued linguistic and cultural knowledge. While the difference in motivations for attending may be evaluated and ranked hierarchically, it does not have a determining impact on fluency. Highlights: Non-Irish learners participate in Irish language immersion events in Ontario. They legitimize their presence in part through access to discourses relating to the antiquity of the Irish language. Their hobby-like connections to the language do not preclude serious commitment to, or fluency in, the Irish language.